Tracing the bongkel: bamboo music of rural farmers in Banyumas, Central Java, Indonesia - Kuwat Kuwat (ASSOCIATION FOR SCIENTIFIC COMPUTING ELECTRICAL AND ENGINEERING (ASCEE), 2021)
Bongkel is the music of a farming community that developed in Gerduren Village, Purwajati, Banyumas, Central Java. This music only uses a four-tone slendro tuning. The current condition is that it is very difficult to find bongkel players; if there is no tracking of information about the history of bongkel, then in the future, it will be very difficult to find important information about bongkel. The purpose of this research is to trace and document the bongkel, from the side of its early history to its musicological review. The research method used is observation and interviews to explore oral sources. The use of oral sources is done because, until now have never received written data that specifically discusses bamboo music, especially in the Banyumas language. The interview focused on Kasmudi, Ibu Kunes, Maryadi Kresek and several other informants who were selected as sources, especially Kasmudi (a bongkel player) because he was the perpetrator the main witness. Kasmudi is the fourth generation of his entire family, which is a bongkel player on average. There are three types of data analyzed, including the history of the appearance of the bongkel, organology data, and musicological data. The grouping of data is done based on the three types of data, and the analysis is done by referring to the grouping of the three types of data. The results of this study found that the strongest characteristic of bongkel music is the imbal technique; besides that, bongkel is one of the musical instruments that became the forerunner to the development of angklung buncis, krumpyung, and calung music. The contribution of this research provides important information for the interest of Banyumas musical studies, especially for the development of bamboo music